HUBUNGAN KARAKTERISTIK KOMITE AUDIT TERHADAPKETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGANPADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - TRI KUSTANTI, AFRIDA (Jurnal Akuntansi AKUNESA, 2015)
The aim of this study examine the relationship of Audit Committee competence, Audit Committee size and Audit Committee meeting to financial report timeliness. This study represent the empirical research which used purposive sampling technique to collect data. Data were collected using secondary data of 71 manufacturing company which listed in Indonesian Stock Exchange 2010-2014. Data analysis uses logistic regression with the program SPSS 21 for windows. The result of this study show that Audit Committee competence, Audit Committee size and Audit Committee meeting are not related to financial report timeliness.Key Word: Audit Committee Competence, Audit Committee Size, Audit Committee Meeting and Financial Report Timeliness.